Enhancing growth and salinity stress tolerance of date palm using Piriformospora indica - Sabeem, Miloofer; Abdul Aziz, Mughair; Mullath, Sangeeta K.; Brini, Faical; Rouached, Hatem; Masmoudi, Khaled (Frontiers in Plant Science, 2022)
Endophytic fungi are known to enhance plant growth and performance under salt stress. The current study investigated the growth, as well as biochemical and molecular properties of Phoenix dactylifera colonized with the mutualistic fungus Piriformospora indica, under control and salinity stress. Our findings indicated an increase in the plant biomass, lateral root density, and chlorophyll content of P. indica-colonized plants under both normal and salt stress conditions. Further, there was a decline in the inoculated plants leaf and root Na+/K+ ratio. The colonization enhanced levels of antioxidant enzymes such as catalase, superoxide dismutase, and peroxidase (CAT, SOD, POD) in plants. Increased ionic content of Zn and P were also found in salt-stressed date palm. The fungus colonization was also associated with altered expression levels of essential Na+ and K+ ion channels in roots like HKT1;5 and SOS1. This alteration improved plant growth due to their preservation of Na+ and K+ ions balanced homeostasis under salinity stress. Moreover, it was confirmed that RSA1 and LEA2 genes were highly expressed in salt-stressed and colonized plant roots and leaves, respectively. The current study exploited P. indica as an effective natural salt stress modulator to ameliorate salinity tolerance in plants.